More than love : an intimate portrait of my mother, Natalie Wood - Wagner, Natasha Gregson, 1970- (Scribner, an imprint of Simon & Schuster, Inc., 2020)
"The heartbreaking, never-before-told story of Hollywood icon Natalie Wood's glamorous life, sudden death, and lasting legacy, written by her daughter, Natasha Gregson Wagner"--